Monetising misfortune: the financial consequences of injuries in professional football teams - Micha Pietzonka; Sören Dallmeyer; Henry Steinfeldt; Timo Hübers; Christoph Breuer (BMJ Open Sport & Exercise Medicine)
Objectives To evaluate the financial impact of player injuries on team performance in German football’s first and second divisions, focusing on the indirect costs related to reduced performance and lost revenue.Method This retrospective, longitudinal study analysed data from seven seasons (2014/2015 to 2020/2021) of the Bundesliga. Injury metrics (incidence, burden and matchday unavailability) were examined using linear mixed models to assess their relationship with team performance (league rank and points). Financial impacts were estimated by translating performance declines into revenue losses from TV broadcasting rights and prize money.Results Findings show a significant negative relationship between most injury measures and team performance across both divisions. In the second division, an additional 333 injury days were associated with a one-rank drop, while the relationship was not statistically significant in the first division. For injury incidence, an increase of 4.33 injured players in the first division and 2.64 injured players in the second division corresponded to a one-rank drop. Matchday unavailability had similarly strong effects: in the first division, an additional 1.62 unavailable players per matchday were linked to a one-rank drop, while in the second division, only 0.71 unavailable players resulted in the same outcome. Financial losses due to injury-related performance declines were substantial, particularly for higher-ranked teams in the first division.Conclusions Injuries significantly affect team performance, causing notable financial losses through reduced league rankings and points.